Dissociation between physical capacity and daily physical activity in COPD patients. A population-based approach. (February 2023) - García-Río, Francisco; Miravitlles, Marc; Soriano, Joan B.; Cosío, Borja G.; Soler-Cataluña, Juan José; Casanova, Ciro; de Lucas, Pilar; Alfageme, Inmaculada; González-Moro, José Miguel Rodríguez; Sánchez Herrero, María Guadalupe; Ancochea, Julio
Abstract: Badkground: Physical capacity (PC) and daily physical activity (PA) are two crucial factors in the clinical course of COPD, although they do not always maintain a close relationship. The objectives were to evaluate the frequency of PC-PA dissociation in patients with COPD and subjects without airflow limitation (AL) and to identify its risk factors. Methods: A sample of 319 COPD patients and 399 subjects without AL was consecutively obtained from a population-based sample of 9092 subjects evaluated in the EPISCAN II study. Baseline evaluation included clinical questionnaires, lung function testing, blood analysis and low-dose computed tomography (CT) scan with evaluation of lung density and airway wall thickness. A distance walked in 6 min > 70% predicted was considered an indicator of normal PC, while a Yale Physical Activity Survey summary index score <51 was used to identify with sedentary lifestyle. Results: 166 COPD patients (52.0%) reported a sedentary lifestyle with evidence of preserved PC, while this phenomenon was present in 188 (47.1%) subjects without AL. In the COPD group, symptoms of chronic bronchitis, depression and elevated hematocrit and blood eosinophil count were identified as independent risk factors for PC-PA dissociation. In turn, in the subjects without AL, the risk factors for PC-PA dissociation were low fat-free mass, obesity and anxiety, as well as reduced levels of HDL-cholesterol and the absence of osteoporosis. Conclusions: Almost half of COPD patients and subjects without airflow limitation with preserved PC maintain a sedentary lifestyle, with different risk factors for sedentarism between both groups. Highlights: Dissciation between physical capacity (PC) and physical activity (PA) is frequent in COPD patients and non-CPD subjects. In COPD patients, chronic bronchitis, depression, increased hematocrit and eosinophils are related to PC-PA dissociation. The risk factors for the PC-PA dissociation are different in patients with COPD and in subjects without airflow limitation.